Bringing Ecology Back: How Can the Chemistry of Indirect Plant Defenses Against Herbivory Be Manipulated to Improve Pest Management? - Furlong, Michael J.; Ang, Gurion C. K.; Silva, Rehan; Zalucki, Myron P. (Frontiers in Plant Science, 2018)
Research on insect-plant interactions has highlighted the intricacies of constitutive and induced plant defences. Of particular interest has been the relationship of natural enemies (especially parasitic hymenoptera) to herbivore induced changes to plants, particularly their responses to herbivore induced plant volatiles (HIPVs). In recent decades this has been a fertile area for research, with elegant experiments showing that HIPVs are important to attracting natural enemies to plants. We critically appraise the application of work on HIPVs in plant-insect-natural enemy interactions. The promise of applications to improved pest management has not been forthcoming. We attribute this to failure to include the multifaceted aspects of natural enemy-prey interactions – attraction, location, subjugation and experience. Attraction in an olfactometer by naïve parasitoids has not been translated to methodologically sound field-based estimates of higher parasitism rates. We highlight what needs to be done to better understand the information that HIPVs convey, how this is utilised by parasitoids and how a greater understanding of these interactions might lead to the development of new strategies so that this knowledge can be effectively deployed for improved pest management.